Effect of Tofu Industrial Liquid Waste Disposal on Well Water Quality: Pengaruh Pembuangan Limbah Cair Industri Tahu Terhadap Kualitas Air Sumur - Nadia Shafa Khairuna; Salsadilla Yasmin Andika Putri; Uniya Azarina; Tri Widayatno (Jurnal Kimia dan Rekayasa, 2022)
The liquid waste of the tofu industry around residential area will affect the quality of their well water. This study was aimed to determine the effect of the tofu industry wastewater on wells located around the tofu industry at different distances. This study took 3 well water samples from 3 well sources with a distance of 10 meters from the tofu industry, 20 meters from the tofu industry, and 30 meters from the tofu industry. The well water samples were examined at the Health Laboratory of Sukoharjo Regency to determine the physicochemical properties such as odor, taste, color, temperature, turbidity, and amount of dissolved solids, such as iron, manganese, chloride, hardness as CaCO3, pH, and sulfate, as well as biological contamination such as coliform and feces. From the results of this study, it was found that the quality of well water around the tofu industry located in Madegondo Grogol Sukoharjo Village is only suitable for bathing and washing but is not suitable for consumption in accordance with the quality standards of clean water quality in accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 32 2017. AbstrakLimbah cair industri tahu yang ada disekitar rumah warga akan mempengaruhi kualitas air sumur warga sekitar. Penelitian ini bertujuan untuk mengetahui pengaruh dari limbah cair industri tahu terhadap sumur yang terletak di sekitar industri tahu tersebut dengan jarak yang berbeda-beda. Penelitian ini mengambil sampel air sumur sejumlah 3 dari 3 sumber sumur dengan jarak 10 meter dari industri tahu, 20 meter dari industri tahu, dan 30 meter dari industri tahu. Sampel air sumur tersebut kami uji di Laboratorium Kesehatan Kabupaten Sukoharjo untuk mengetahui kelayakan fisik seperti bau, rasa, warna, suhu, kekeruhan, dan jumlah zat padat terlarut, kelayakan kimiawi seperti besi, mangan, khlorida, kesadahan sebagai CaCO3, pH, dan sulfat, dan kelayakan bakteriologi seperti coliform dan colitinja. Dari hasil penelitian tersebut didapatkan hasil bahwa kualitas air sumur di sekitar industri tahu yang terletak di Desa Madegondo Grogol Sukoharjo hanya layak digunakan untuk mandi dan mencuci namun tidak layak untuk dikonsumsi sesuai dengan standar baku mutu kualitas air bersih sesuai dengan Peraturan Menteri Kesehatan Republik Indonesia Nomor 32 Tahun 2017.